DEMOCRACY GAMPÔNG AS AN INITIATIVE TO ELLIMINATE MONEY POLITICS IN ACEH SINGKIL - Effendi Hasan; Muliawati Muliawati; Helmi Helmi; Ikhsan Ikhsan; Vellayati Hajad (JWP (Jurnal Wacana Politik), 2023)
ABSTRACT. Money politics conducted by political actors has inadvertently harmed the order of democratic civilization, which seeks to produce exemplary leaders with competence and morality. The practice of money politics is still prevalent in the local community of Singkil Regency, where it is considered pervasive. This is evident in every political contest for the Pileg and Pilkada, where candidates distribute cash, goods, and basic necessities. Observations on the ground indicate that there is a strong suspicion that the people there are extremely pragmatic in their political choices; they do not see the potential figures of the candidates but rather candidates who can give money to the people they favor. For the analysis of the aforementioned issues, a qualitative method involving observation, interviews, and documentation was employed. The study’s conclusion demonstrates that money politics is a form of buying and selling votes, which is one of the issues that must be addressed in general elections. However, state election supervisors in the regions, such as Panwaslih, continue to have limited manpower, time, and resources to oversee the practice of money politics during elections. As a result, the establishment of Gampông Politik as a socio-political institution is an important strategy for eradicating money politics by instilling democratic values, providing political education, and enforcing the law.